Modeling approaches to investigate the interaction between Fullerene and β-Amyloid (Research, Society and Development, 2021)
Alzheimer's disease is the progressive loss of mental function, characterized by degeneration of brain tissue, including the loss of nerve cells, the accumulation of an abnormal protein called β-amyloid, and the development of neurofibrillary tangles. β-amyloid aggregation is a physiological feature of Alzheimer's disease and is closely related to neurodegeneration caused by Alzheimer's. Recently, new therapies are looking for promising compounds capable of breaking down β-amyloid. Nanoparticles (NPs) are highly promising candidates for several important biological applications such as gene delivery, cell imaging and tumor therapy. Among numerous types of nanomaterials, carbon NPs have attracted particular interests, such as: zero-dimensional fullerene, one-dimensional (1D) carbon nanotubes and two-dimensional (2D) graphene. Because of this, we used molecular docking to investigate the interaction capacity of the fullerene nanoparticle with the β-amyloid aggregate. The docking results showed that the main interactions established were hydrophobic. The System had an affinity energy of -41.04 Kcal, obtained with the MM-GBSA method.